1998
DOI: 10.1016/s0009-9236(98)90102-3
|View full text |Cite
|
Sign up to set email alerts
|

The pharmacokinetics of a single oral dose of mycophenolate mofetil in patients with varying degrees of renal function*

Abstract: Clearance of mycophenolic acid after a single 1 gm oral dose of mycophenolate mofetil is unaffected by renal function. Clearance of mycophenolic acid is unaffected by hemodialysis. Diminished renal function should not require preemptive adjustment of 1 gm doses of mycophenolate mofetil; however dosage adjustment may be warranted on the basis of adverse effects or toxicity in individual patients. Mycophenolate mofetil can be administered irrespective of hemodialysis session without effect on mycophenolic acid e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
48
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(57 citation statements)
references
References 8 publications
7
48
2
Order By: Relevance
“…[30][31][32] We observed that there was a positive correlation between MPA and MPAG C 0 and serum creatinine concentration. C 0 of MPA and MPAG was influenced by renal function in CyA-treated recipients but not in those treated with TAC.…”
Section: Discussionmentioning
confidence: 60%
“…[30][31][32] We observed that there was a positive correlation between MPA and MPAG C 0 and serum creatinine concentration. C 0 of MPA and MPAG was influenced by renal function in CyA-treated recipients but not in those treated with TAC.…”
Section: Discussionmentioning
confidence: 60%
“…Neither for RTX nor for AID a relationship between MMFdose per body weight and MPA-PK was found, suggesting that the initiation of MMF treatment in adults with a body weightadapted dosage is not of advantage compared with a fixed standardized dose. According to observations in transplant recipients (25), MPAG-AUC increased in both patient groups as renal function diminished. A higher glucuronidation of MPA has been described in male than in female RTX patients (30).…”
Section: Discussionmentioning
confidence: 89%
“…For example, some studies found that impaired renal function and low albumin levels result in high total MPA clearance and thus low total MPA exposure (5,9,11,13,14), although this could not be confirmed in all stud-ies (15)(16)(17)(18)(19)(20). Also with regard to the effect of the use of comedication (3,10,18,21,22), diabetes (23,24), body weight (11,13,17,20), age (5,11,18 -20), gender (11,20,23), and race (9,23,25), contrasting results have been obtained. Most of these studies were underpowered, based on MPA predose levels only, and some studies did not control adequately for confounding factors.…”
mentioning
confidence: 96%